Disability profiles and needs of disability grant recipients in Kleinmond, Western Cape, South Africa / Annette Freig. - Frieg, Annette (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil (Rehabilitation))--University of Stellenbosch, 2000.